Keluarga, kontrol sosial, dan âstrainâ : model delinquency remaja - Purwandari, Eny (HUMANITAS (Jurnal Psikologi Indonesia), 2011)
Behavior emerges from a continuous process, which begins with theindividuals perception, internalization of the concept, to the covert behavior.Behavior is the result of experience. This study aims to test models ofdelinquency. Delinquency as a continuous learning process of behaviorfrom mild to serious. The subjects were junior and high school students asmany as 182 people from 3 schools that obtained by random. The datawere analyzed using structural equation modeling (SEM) showed thatdelinquency was a behavior that basically formed an ongoing basis. Familieshave the highest impact when compared with peers and the media.Conditions will be worsened if the child has a strain in delinquency bringlight and progress to serious delinquency.